An energy-efficient DAC switching algorithm based on charge recycling method for SAR ADCs. (December 2018) - Akbari, Meysam; Hashemipour, Omid; Khateb, Fabian; Moradi, Farshad
Abstract: This paper configures a successive approximation register (SAR) analog-to-digital converter (ADC) based on a new switching algorithm with efficient energy consumption. The proposed switching algorithm applies the same reference voltage to the bottom plates of all capacitors in each capacitor array to drain no energy through capacitors. In addition to a 100% energy saving in the switched-capacitor digital-to-analog converter (DAC) block, configuration of an N -bit SAR ADC shows a 50% capacitor area reduction in comparison with the conventional SAR ADC.